Carbonation of Steel Slag: Testing of the Wet Route in a Pilot-scale Reactor. (July 2017) - Librandi, Paola; Costa, Giulia; Souza, Ana Carolina Bello de; Stendardo, Stefano; Luna, Aderval Severino; Baciocchi, Renato
Abstract: This work reports the first results of an on-going activity aimed at the scale up of the wet-route carbonation of steel slag for storing CO2 and generating a product with valorization potential. Two batches of Basic Oxygen Furnace slag (BOF1 and BOF2) collected at different times from a steelmaking plant downstream iron recovery were used to perform the tests in a pilot-scale rotary kiln unit part of ENEA's research infrastructure. The tests were carried out at ambient (25 °C- 37 °C) and enhanced temperature (45 °C-53 °C), under a 40-47% CO2 flow, at atmospheric pressure for a reaction time of 30 min. In each experiment around 1000-1500 g of BOF slag was employed. The residues were humidified in order to achieve a liquid to solid ratio of 0.17 l/kg. This value was selected on the basis of the results of preliminary lab-scale static and dynamic experiments that are also presented in this paper. The product collected at the end of each test was cured at controlled conditions (T=25 °C e RH=100%) for 28 days and then characterized in terms of particle size, CO2 uptake and environmental behavior. The mean diameter (D50 ) of the obtained product was around 1 mm for the tests performed at room temperature and slightly lower for the test performed at 50 °C, i.e. around twice the size of the starting material. The CO2 uptake measured for samples collected immediately after the tests was quite similar (4-6% wt.), whereas after curing a 50% increase was observed for all BOF1 slag samples, while only a slight increase was observed for BOF2 slag. These results are significantly higher than the ones of the lab-scale tests. The leaching behavior of the product appeared also to be significantly affected by the treatment performed in the pilot plant.